Analysis of Treatment Unit Selection in The Design of The Water Treatment Plant (III) Karawang Branch, East Karawang District - Liandi, Malvin; Hadisoebroto, Rositayanti; Winarni, Winarni (Fakultas Teknik, Universitas Pasundan, 2025)
The Drinking Water Treatment Plant (III) Karawang Branch was developed to increase production capacity and ensure an adequate water supply for the Karawang Service Area. The raw water for this plant is sourced from the West Branch North Tarum Channel (STUB) and has a design production capacity of 100 L/s. The design aims to implement optimal treatment processes to meet the required drinking water quality standards. This study investigates the selection of treatment units for the plant, focusing on raw water quality as the primary criterion to meet the drinking water standards stipulated by Ministry of Health Regulation No. 2 Year 2023. Key water quality parameters that do not meet these standards include total suspended solids (TSS), total dissolved solids (TDS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), dissolved oxygen (DO), sulfide, color, detergent, fecal coliform, and total coliform. The selection of treatment units was conducted using the Water Quality-Based Approach, which considers specific contaminants in the raw water, along with the Literature-Based Approach, involving a review of existing water treatment plants and their efficiency in similar settings. The chosen treatment units include an intake system, hydraulic coagulation, hydraulic flocculation, sedimentation with plate settlers, dual-media rapid sand filtration, chlorination disinfection, and a ground reservoir for water storage. This study contributes to ensuring a sustainable and safe drinking water supply for the Karawang region through an integrated water treatment system.